UJICOBA Model rehabilitasi berbasis masyarakat dalam penanggulangan napza / Daud Bahransyaf...[et al] ; editor, C. Elly Kumari Tjahja Putri - Bahransyaf, Daud; Putri, C. Elly Kumari Cahya (2010)
VIII, 210 hlm ilus 21 cm